Combination of P300 and CSF β-Amyloid(1-42) Assays May Provide a Potential Tool in the Early Diagnosis of Alzheimer's Disease - Papaliagkas, V.T.; Anogianakis, G.; Tsolaki, M.N.; Koliakos, G.; Kimiskidis, V.K. (Current Alzheimer Research, 2010)
Background/Aims. The aim of this study was to investigate the diagnostic role of CSF β-amyloid(1-42) levels and auditory event-related potentials (AERPs) in the progression of mild cognitive impairment (MCI) to Alzheimer's disease (AD). Methods. In fifty three MCI patients (group 1) a lumbar puncture was performed and β-amyloid(1-42) levels were determined. Twenty patients (group 2) were re-examined after 11 months. During this period five of them progressed to AD. Neuropsychological and ERP examinations were performed in all patients at both exams. Results. Compared to MCI-stable patients, AD-converters showed significantly lower β-amyloid(1-42) values both for group 1 (Mann Whitney test, Z=-2.952, p=0.003; effect size r=-0.41) and group 2 (Z=-2.458, p=0.011; effect size r=- 0.55). On the other hand, the patients of group 1 who converted to AD had prolonged latencies and lower amplitudes of the P300 wave compared to those of the MCI-stable patients, although the differences were not significant. Conclusions. Compared to the separate use of CSF β-amyloid(1-42) and AERPs, higher values of sensitivity and specificity were achieved by the combined use of β-amyloid(1-42) levels and P300 latencies (80% and 98%) or amplitudes (100% and 89%) in the discrimination between AD-converters and MCI-stable patients. Therefore the combination of an electrophysiological and a biological marker is potentially of high diagnostic value for the early diagnosis of AD-converters.
Keywords: β-amyloid(1-42)